PENERAPAN MODEL PEMBELAJARAN GUIDED INQUIRY UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATERI SISTEM EKSKRESI PADA SISWA KELAS XI IPA ICT SMAN KEBAKKRAMAT - Qodarnisa Prehtiningsih; Murni Ramli; Nurmiyati Nurmiyati (BIO-PEDAGOGI, 2015)
The purposes of this action research are (1) to improve the concept understanding on excretion system through the implementation of guided inqury learning model, (2) to know the influence of guided inquiry learning model toward students concept understanding on excretory system, and (3) to know the level of student understanding on excretory system concepts. This study is an action research (Classroom Action Research) was carried out in three cycles. Each cycle consists of four stages: planning, action, observation, and reflection. The subjects were students of class XI IPA ICT SMAN Kebakkramat in academic year 2013/2014. Data were obtained through cognitive tests, observations, and interviews. Data analysis techniques using qualitative descriptive analysis techniques. Data validation using triangulation techniques. The results showed an increase in students' understanding of concepts for each sub subject of Excretory System. The level of understanding of the concept increased by 33.7% in the sub subject of skin excretory system, 8.93% in sub subject excretory system of the lungs, 22.62% in sub subject of renal excretory system, 20.7% in the sub-principal discussion liver excretory system, 8.93% in sub subject excretory system disorders, and 17.27% in sub subject of animal excretion system. Based on the results of this study concluded that learning through Guided Inquiry models can enhance students' understanding of the concept of excretory system grade XI IPA ICT SMAN Kebakkramat in academic year 2013/2014. Keywords : Guided Inquiry Learning Model, Understanding Concept